Laser lipolysis with a 980-nm diode laser: experience with 400 cases - Valle Dornelles, Rodrigo de Faria (2014)
Introduction: Liposuction has undergone several improvements since its first description, including changes in the cannulas, variation in the concentration of the infiltrating solution, and the use of different devices and technologies. The use of laser technology devices for lipolysis and stimulation of skin retraction has contributed to the procedure. This article presents the authors’ experience with laser lipolysis in 400 patients, within a 5-year period, and discusses the principles of the technology and its effect on tissues. Methods: This is a study performed between July 2007 and July 2012 and included 400 patients who underwent laser lipolysis. All procedures were performed following the original protocol – infiltration of cold saline, passage of the cannula with an optic fiber for conducting the energy needed for laser lipolysis, skin retraction, and finally, conventional liposuction. Results: Hospitalization type ranged from outpatient to overnight surgery. Approximately 45% (180 of 400) of patients had minimal bruising, with involvement of 2% or more of the affected body surface. Hematoma, seroma, and dehiscence occurred in a total of 9% (36 of 400) of patients. We did not find any case of thermal burn of the skin. Conclusions: Laser lipolysis performed according to the described technique was safe and reproducible.